Incorporating neglected non-communicable diseases into the national health program—A review - Sudip Bhattacharya; Petra Heidler; Petra Heidler; Petra Heidler; Saurabh Varshney (Frontiers in Public Health, 2023)
Poor nations are already facing the heat of double burden of communicable and non-communicable diseases (NCDs), often known as chronic illnesses, which are characterized by a protracted course and are multifactorial in causation. In addition to this, neglected non-communicable diseases (NNCD) in the form of gout, sickle cell disease, accidents and many more are likely to be one of the biggest public health challenges soon. Nearly three-quarters (31.4 million) of all NCD-related fatalities occur in developing nations. In terms of morbidity and mortality, the “BIG FOUR” NCDs—diabetes, cancer, chronic respiratory diseases, and cardiovascular diseases—are widely acknowledged as the main contributors to global health loss. However, other NCDs account for 55% of the global burden of NCDs and are frequently neglected in terms of premature death, increased Disability Adjusted Life Years (DALY), and decreased Quality-Adjusted Life Year (QALY). We have briefly discussed the disease burden of a few significant, yet neglected NCDs in this paper.